Designing Parahyangan Animation Center Futuristic Architecture Theme - Sandi Solehudin; Arief Perdana Putra; Wowo Adizar Darwin (Jurnal Arsitektur Archicentre, 2023)
The improvement of activity animation industry is developing step by step, alongside various new advancements that help the current liveliness progress. Activity is chosen because it can be a way to convey data through movies so that it is clearer. Meanwhile, modern advancement in Indonesia is rather slow so it is overwhelmed by the outside nations that occupied the developing areas first. However, in recent times, the domestic activity industry has grown through the movement of conveying social, cultural, and historical themes. Although constrained in terms of adequate, the human resources in Indonesia can be said to be very satisfactory. Therefore, this planning can be relied upon to enable all kinds of activeness sports in Indonesia as well as activities to get to know a wider area. Using the concept of the Smart Building approach can help support the creation of animations, which can help present an interesting perception with the use of efficient power for animation production.